2006
DOI: 10.1128/aac.50.4.1183-1194.2006
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus CcpA Affects Virulence Determinant Production and Antibiotic Resistance

Abstract: Carbon catabolite protein A (CcpA) is known to function as a major regulator of gene expression in different gram-positive organisms. Deletion of the ccpA homologue (saCOL1786) in Staphylococcus aureus was found to affect growth, glucose metabolization, and transcription of selected virulence determinants. In liquid culture, deletion of CcpA decreased the growth rate and yield; however, the effect was only transient during the exponential-growth phase as long as glucose was present in the medium. Depletion of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
193
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 186 publications
(215 citation statements)
references
References 63 publications
21
193
1
Order By: Relevance
“…5B). In line with our previous findings (7,14), we found a significant increase in citZ transcription in the ccpA mutant KS66 in the early exponential growth phase (i.e. after 3 h of growth in TSB supplemented with 0.1% (w/v) of glucose), whereas transcription of hla, which is expressed mainly during the later stages of growth, was markedly down-regulated in KS66 after 8 h of growth compared with the wild type.…”
Section: Resultssupporting
confidence: 79%
See 3 more Smart Citations
“…5B). In line with our previous findings (7,14), we found a significant increase in citZ transcription in the ccpA mutant KS66 in the early exponential growth phase (i.e. after 3 h of growth in TSB supplemented with 0.1% (w/v) of glucose), whereas transcription of hla, which is expressed mainly during the later stages of growth, was markedly down-regulated in KS66 after 8 h of growth compared with the wild type.…”
Section: Resultssupporting
confidence: 79%
“…With the present study, we extend previous work demonstrating the regulatory role of Stk1-mediated phosphorylation in central metabolism and virulence pathways by providing first evidence of a Ser/Thr kinase phosphorylation-dependent regulation of the major transcriptional regulator CcpA. This mechanism is of special relevance as CcpA contributes to the pathogenicity of S. aureus (7,8,12,14,15). We demonstrated that phosphorylation of Thr-18 and Thr-33 residues abrogated CcpA DNA binding activity in vitro.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Perhaps the most consistent transcriptional change observed for VISA strains is the downregulation of the spa gene (74,122,169,199,201,251,303). A possibly incomplete list of genes where the gene product has been shown to affect the transcription of spa includes agr (76,343), sarA (51,76,343), sarS (50), arlSR (85,86), sarT (304), srrAB (262), tcaR (200), mgrA (138), rot (240), ccpA (307), and sarZ (342). Potentially, a mutation in any of these regulatory genes could simultaneously increase vancomycin resistance and decrease protein A production.…”
Section: Molecular Mechanisms Of Resistancementioning
confidence: 99%